Exploring Pathogenesis, Clinical Manifestations, and Management of Human Metapneumovirus Infection - Damre, Gaurao; Sathe, Snehal; Shinde, Dhanashree; Bhone, Vaibhav V (Journal of Pharmacy Practice and Community Medicine, 2026)
Human Metapneumovirus (HMPV), identified in 2001, is an emerging respiratory virus. Within the Pneumoviridae family, genus Metapneumovirus. This RNA virus is now recognised as a substantial cause of both upper along lower Respiratory Tract Infections (RTIs), affecting individuals belonging to all ages. While this virus may impact healthy adults, the most vulnerable populations include young children, infants, elderly adults, as well as immunocompromised individuals. Pathophysiology of HMPV involves its entry into respiratory epithelial cells, facilitated by viral Fusion (F), attachment (G) proteins. After entering the host cell, HMPV replicates in the cytoplasm, leading to the production of new virions that further propagate the infection. Both innate along adaptive components are essential to the complicated immune response to HMPV. Innate immunity, including pattern recognition receptors and natural killer cells, provides the first line of defence, while the adaptive immune response, consisting of T cells, antibodies, and B cells, is responsible for clearing the virus and offering long-term immunity. However, in severe cases, immune responses may contribute to lung injury, airway remodelling, and fibrosis, especially in individuals with pre-existing conditions or those experiencing prolonged infections. Clinically, HMPV infection varies from mild symptoms like cough, fever, as well as sore throat to more severe manifestations, for example, pneumonia, bronchiolitis, and respiratory failure. Supportive care, which includes hydration, is the main emphasis of management and rest, though antiviral treatments, for example, intravenous immunoglobulin, ribavirin, along with monoclonal antibodies, may be considered in severe cases.
Keywords: Fusion Protein (Human Metapneumovirus) HMPV; Immunoglobulins; RNA; Interference; Respiratory syncytial virus; Ribavirin